Werden die Regelungen des Familienrechts heutigen Familien und Kindern gerecht? Reflexionen aus sozialwissenschaftlicher Perspektive - Laszlo A. Vaskovics; Johannes Huinink (Journal of Family Research, 2016)
The fast increasing diversity of family patterns and family structures, new constellations of parenthood and relations to child as well as accompanying changes in family relations constitute challenges for both legislation and jurisdiction. Among family law professional, this statement does not provoke any controversy. It remains controversial among them, however, if and how legislation should react to these changes. Similar discussions exist in the literature of the social sciences, where diverging assessments and positions are presented. In this contribution, the discussion shall be carried on by asking: Do the provisions in German family law still meet the needs of families and children? Taking the jurisprudential contributions to this special issue as well as recent jurisprudential debates into account, legal loopholes are to be identified and solutions from a social science perspective are proposed. Additionally, it will be critically discussed, where the bridging of legal gaps by further differentiation and expansion of family law – for taking new parenthood and family constellations into account – may lead to. From a social science perspective, are there serious concerns to be raised with regard to the path already entered? Do alternative, not yet considered, routes for meeting the challenges possibly exist? These questions take center stage in the last chapter of this concluding contribution.